ANALISIS EFEKTIVITAS PEKERJAAN PENANGANAN JALAN LONG SEGMENT DI JALAN KAPTEN BUKHARI GUNUNG MESIR (DAK) KABUPATEN BENGKULU SELATAN (Inersia: Jurnal Teknik Sipil, 2025)
South Bengkulu Regency is rich in economic potential in the agriculture, plantation, fisheries, and tourism sectors. Adequate roads are key to optimizing this potential. Recognizing this, the South Bengkulu Regency Government has initiated a project to handle long segments on Jl. Kapten Bukhari Gunung Mesir, funded by the Special Allocation Fund (DAK). This report examines the conformity of project planning with the results achieved, as well as the conformity of the implementation schedule with the time required. This evaluation includes a comparison of the results of the work with the initial Budget and Cost Plan (RAB) and a comparison of the implementation time with the original plan. The evaluation results show that the project is in line with the initial plan, both in terms of the volume of work and the completion time. This has resulted in a significant improvement in road quality. Technical constraints such as bad weather and limited material availability were overcome with effective solutions. The project has generated significant economic and social benefits for the community, such as improved accessibility, time efficiency, and increased safety. Recommendations for future projects include improved coordination, more flexible schedule adjustments, better public awareness, regular monitoring and evaluation, capacity building, and more optimal risk management. Keywords: Road Infrastructure, Road Rehabilitation, Road Reconstruction, Budget and Cost Plan, S-Curve (Time Schedule)